2012
DOI: 10.1051/0004-6361/201118347
|View full text |Cite
|
Sign up to set email alerts
|

Spectral line survey of the ultracompact HII region Monoceros R2

Abstract: Context. Ultracompact (UC) Hii regions constitute one of the earliest phases in the formation of a massive star and are characterized by extreme physical conditions (G 0 > 10 5 Habing field and n > 10 6 cm −3 ). The UC Hii Mon R2 is the closest example and an excellent target to study the chemistry in these complex regions. Aims. Our goal is to investigate the chemistry of the molecular gas around UC Hii Mon R2 and the variations caused by the different local physical conditions. Methods. We carried out 3 mm a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
73
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 43 publications
(87 citation statements)
references
References 57 publications
12
73
2
Order By: Relevance
“…C 2 H has been detected toward other PDRs with various physical conditions, including Mon R2 (Rizzo et al 2005;Ginard et al 2012;Pilleri et al 2013), the Horsehead PDR (Teyssier et al 2004;Pety et al 2005), and NGC 7023 (Fuente et al 1993). Similar to what we found for the Orion Bar, multiple C 2 H transitions measured toward Mon R2 also suggest a two-component fit to describe C 2 H toward this region (Pilleri et al 2013).…”
Section: Discussionsupporting
confidence: 83%
“…C 2 H has been detected toward other PDRs with various physical conditions, including Mon R2 (Rizzo et al 2005;Ginard et al 2012;Pilleri et al 2013), the Horsehead PDR (Teyssier et al 2004;Pety et al 2005), and NGC 7023 (Fuente et al 1993). Similar to what we found for the Orion Bar, multiple C 2 H transitions measured toward Mon R2 also suggest a two-component fit to describe C 2 H toward this region (Pilleri et al 2013).…”
Section: Discussionsupporting
confidence: 83%
“…However, it might be less likely that Clump 1 is a PDR, since SO 2 tend to be easily dissociated in a PDR (e.g. Fuente et al 2003;Ginard et al 2012). Further observations will make it clear which picture can explain what takes place in Clump 1.…”
Section: The Localization Of Hot Molecular Gases and Chemically Rich mentioning
confidence: 97%
“…It thus is likely that the beam dilution will affect the line luminosities and then the derivation of column densities. Beam dilution can be more easily disentangled from excitation effects when several lines of different energy levels and critical densities Goicoechea et al (2006). happen at close by frequencies so that the beam dilution is identical for these lines. However, we cannot derive source properties below the lowest measured angular resolution without an a priori analytical model of the source spatial distribution.…”
Section: Beam Dilutionmentioning
confidence: 99%
“…CH 3 CN and HC 3 N were detected in the Mon R2 ultracompact H ii region (Ginard et al 2012). Mauersberger et al (1991) reported the first detection of CH 3 CN in M 82 and NGC 253.…”
Section: Introductionmentioning
confidence: 98%